Role of Self-Efficacy and Resistance to Innovation on the Demotivation and Insufficient Learning Capabilities of Preservice English Normal Students in China - Lu, Tuanhua; Sanitah, Mohd Yusof; Huang, Yongliang (Frontiers in Psychology, 2022)
Learning capabilities among students are the crucial element for the student's success in learning a particular language, and this phenomenon needs recent studies. The current study examines the impact of self-efficacy and resistance to innovation on the demotivation and insufficient learning capabilities of pre-service English normal students in China. The current research also investigates the mediating impact of demotivation among self-efficacy, resistance to innovation and insufficient learning capabilities. The questionnaires were employed by the researchers to gather the data from chosen respondents. The SPSS-AMOS was applied to test the relationships among variables and also test the hypotheses of the study. The results revealed that self-efficacy and resistance to innovation have a significant and a positive linkage with demotivation and insufficient learning capabilities. The findings also indicated that demotivation significantly mediates among self-efficacy, resistance to innovation and insufficient learning capabilities. This study helps the policymakers to establish the regulations related to the improvement of learning capabilities using innovation adoption and motivation of the students.